Pengaruh Motivasi Intrinsik, Kepemimpinan Transformasional dan Komitmen Organisasi Terhadap Kinerja Karyawan - Billa Laura Ashari; Dewi Andriani; Vera Firdaus (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2025)
The purpose of this study was to analyze the effect of intrinsic motivation, transformational leadership, and organizational commitment on employee performance in umkm. The research attempted by the author in this research is quantitative descriptive research, in quantitative descriptive research using the total sampling method in collecting information. The umkm that will be carried out this research is umkm kampung pia which is located in Warurejo Village, Gempol District, Pasuruan Regency. The population in this study were employees who worked at the UMKM Kampung Pia Warurejo Village. The sample of this study was purposive sampling method obtained from a total sample of 90 respondents. this study uses primary data questionnaires with a Likert scale which are processed using smartpls. the results obtained are intrinsic motivation affects employee performance, transformational leadership affects employee performance and organizational commitment affects employee performance in umkm.